The environmental effects of aerodynamic interference between two closely positioned irregular high buildings. Issue 180 (September 2018) - Flaga, Andrzej; Kocoń, Agnieszka; Kłaput, Renata; Bosak, Grzegorz
Abstract: The close proximity of high buildings in urban areas causes significant interference effects to occur between them. Commonly, it has an adverse effect upon wind conditions in such areas. Taking into account the increasingly dense arrangement of buildings in cities, this problem will most likely become more significant in future years. Aerodynamic interference has been analysed in many research papers; however, it usually focusses only on the influence of particular variables on the phenomenon. This paper provides a more comprehensive approach, taking into account a case study of irregularly shaped tall buildings. Aerodynamic interference is considered in three aspects: mean pressure distribution on external surfaces, aerodynamic global forces and pedestrian wind comfort. Measurement results clearly show that the orientation of the interfering building and its surroundings with respect to wind direction is crucial for the effects of aerodynamic interference. It is also concluded that the close proximity of two buildings causes high values of negative pressure on walls facing a gap. Nevertheless, at the same time, the shielding effect of the interfering building decreases with regard to the global wind action on the analysed building. Highlights: Comprehensive approach of aerodynamic interference analysis was presented. Local wind pressure, global wind forces and pedestrian wind comfort were considered. Aerodynamic interference change local and global wind action on the building. Pedestrian wind comfort should be considered before planning buildings arrangement.